2005
DOI: 10.1111/j.1479-828x.2005.00452.x
|View full text |Cite
|
Sign up to set email alerts
|

Oronasopharyngeal suction versus no suction in normal, term and vaginally born infants: A prospective randomised controlled trial

Abstract: This prospective randomised controlled trial aimed to compare the effects of oronasopharyngeal suction with those of no suction in normal, term and vaginally born infants and was performed at a Turkish tertiary hospital from June 2003 to January 2004. A total of 140 newborns were enrolled in the trial (n = 70 per group). The no suction group showed lower mean heart rates through the 3rd and 6th minutes and higher SaO(2) values through the first 6 mins of life (P < 0.001). The maximum time to reach SaO2 of >or=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 19 publications
(29 reference statements)
1
34
0
3
Order By: Relevance
“…Neonates in the "no suction" group had significantly lower HR values at 3 and 6 min after birth and significantly higher SpO 2 levels for the first 6 min after birth [18]. In addition, "no suction" group reached SpO 2 levels of ≥92% faster compared to the ONPS group [18]. The same group compared "no suction" versus ONPS in 140 term neonates delivered by cesarean section [7].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Neonates in the "no suction" group had significantly lower HR values at 3 and 6 min after birth and significantly higher SpO 2 levels for the first 6 min after birth [18]. In addition, "no suction" group reached SpO 2 levels of ≥92% faster compared to the ONPS group [18]. The same group compared "no suction" versus ONPS in 140 term neonates delivered by cesarean section [7].…”
Section: Discussionmentioning
confidence: 90%
“…Gungor et al compared 140 vaginally born term neonates, which were randomized to no suction or ONPS. Neonates in the "no suction" group had significantly lower HR values at 3 and 6 min after birth and significantly higher SpO 2 levels for the first 6 min after birth [18]. In addition, "no suction" group reached SpO 2 levels of ≥92% faster compared to the ONPS group [18].…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies also reported similar findings, but the time to reach 92 % saturation was much lesser in the no suction group (6.8±1.8 minutes) than the suction group (10.2 minutes±3.3). 8,11,12 But, in the present study the median difference was only 1 minute 6 seconds ahead in the wipes group. One small trial reported bradycardia in the routine Suction group while in a RCT by Gungor et al, reported lower mean heart rates in the No-Suction group.…”
Section: Discussionmentioning
confidence: 43%
“…This is based on previous trials reporting it as the lowest acceptable saturation value in term neonates at birth. 8,11,12 In another trial, the mean respiratory rate in the first 24 hrs was used as the primary outcome. 13 The Pulseoximeter used in 2005 by Gungor and associates was system III, infant monitor, Air shields, USA) for monitoring and measurements were documented minutes by minutes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation